2016
DOI: 10.1016/j.dark.2016.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Direct reconstruction of dynamical dark energy from observational Hubble parameter data

Abstract: Reconstructing the evolution history of the dark energy equation of state parameter w(z) directly from observational data is highly valuable in cosmology, since it contains substantial clues in understanding the nature of the accelerated expansion of the Universe. Many works have focused on reconstructing w(z) using Type Ia supernova data, however, only a few studies pay attention to Hubble parameter data. In the present work, we explore the merit of Hubble parameter data and make an attempt to reconstruct w(z… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…4. Taking into account that age of the Universe in the standard cosmology is, roughly speaking, inversely proportional to the present-day value of the Hubble parameter, T * ≈ 1/H 0 , we see that our relation (10) predicts that T ≈ (T * /τ ) T * . Since T * ≈ 4•10 17 s, and τ = 5•10 −44 s, this age in our model will be increased by (T * /τ ) ≈ 10 61 times.…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…4. Taking into account that age of the Universe in the standard cosmology is, roughly speaking, inversely proportional to the present-day value of the Hubble parameter, T * ≈ 1/H 0 , we see that our relation (10) predicts that T ≈ (T * /τ ) T * . Since T * ≈ 4•10 17 s, and τ = 5•10 −44 s, this age in our model will be increased by (T * /τ ) ≈ 10 61 times.…”
Section: Discussionmentioning
confidence: 75%
“…While in the standard cosmology the Hubble parameter either remains constant with time (when evolution is determined by the Λ-term) or decays as α/t (where α = 1/2 when radiation dominates, and α = 2/3 when a non-relativistic matter dominates), our equation(8)predicts the inverse square-root dependence H(t) ∝ 1/ √ t, i.e., again some intermediate case between the two extremal situations. Taking into account that age of the Universe in the standard cosmology is, roughly speaking, inversely proportional to the present-day value of the Hubble parameter,T * ≈ 1/H 0 , we see that our relation(10) predicts that T ≈ (T * /τ ) T * . Since T * ≈ 4·10 17 s, and τ = 5·10 −44 s, this age in our model will be increased by (T * /τ ) ≈ 10 61 times.…”
mentioning
confidence: 73%
See 1 more Smart Citation
“…Particularly, in standard cosmology, derived from GR, the dark energy and dark matter should compose ∼ 95% of the universe (Hinshaw et al (2013)), but their nature is still dubious (Dil (2017); Behrouz et al (2017); Germani (2017); Jennen & Pereira (2016); Evslin (2016); Liu et al (2016); Rinaldi (2017); Zhang (2017); Albert et al (2017)).…”
Section: Introductionmentioning
confidence: 99%
“…[5,6]. Yet another popular explanation is a modification of the dark-energy equation-of-state parameter w (where p = wρ) [7,8,9,10]; though the resulting values w < −1 look quite suspicious from the viewpoint of general physical principles. 1 However, from our point of view, the spread in values of H 0 can have a much more straightforward explanation, following from the recent observations of the rotation curves in distant galaxies [12,13]: it was found that the amount of dark matter is considerably less in the vicinity of galaxies located at large redshifts, z = 0.6−2.6.…”
mentioning
confidence: 99%